PROBLEMATIKA HUKUM PERKAWINAN (Analisis Terhadap Ketentaun Pencatatan Perkawinan dalam Perudang-Undangan Islam Indonesia dan Malaysia) - HENDRI K (Fakultas Syariah dan hukum Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
ABSTRACTThe marriage registration provisions have long been established. It can be seen from the birth of Law No. 22/1946 concerning marriage registration, divorce, and referral. These provisions were strengthened through Law No. 1/1974, and then it is strengthened again in Islamic Law Compilation (KHI). Likewise in Malaysia, marital condition that must be registered has been long enacted in the marriage law and the marriage certificate. But until now, in Indonesia and Malaysia, the practice of marriage has not been carried out in the presence of marriage registrar employees.This paper is intended to find out why there are still many unregistered marriages in Indonesia and Malaysia. This research is qualitative in the sense that this research is not to find out how many (quantity) people who have unregistered marriages in Indonesia and Malaysia, but rather this study is intended to examine in-depth why there are still many unregistered marriages in Indonesia and Malaysia, then what are the solutions to marriages have not been recorded.The findings of this research indicate that the number of unregistered marriages in Indonesia is caused by some factors. First: The ambiguity of marriage registration regulation in the legislation. Second: Weak legal sanctions against perpetrators. The current legal sanctions have more impact on wives and children who were born while the husbands hardly feel the negative effects. While in Malaysia, although the rules contained in the enactment and the deed of law are very strict in regulating that the marriage is recorded, there is a legal loophole that is exploited by the Malaysians, which is being able to get married in a place more than two marhalah, then the marriage can be re-registered after first going through the trial process and paying a fine in the Sharia Court.ABSTRAK Ketentuan pencatatan perkawinan telah lama diundangkan setidaknya dapat dilihat dari lahirnya UU No 22/ 1946 tentang Pencatatan Nikah, Talak dan Rujuk. Ketentuan tersebut diperkukuh eksitensinya lewat UU No 1/ 1974, kemudian diperkuat lagi dalam KHI. Begitu juga di Malaysia ketentuan perkawinan harus didaftarakan sudah lama diundangkan dalam enakmen maupun akta undang-undang perkawinan, namun hingga kini di Indonesia maupun Malaysia praktek perkawinan tidak dihadapan pegawai pendaftar perkawinan masih banyak dijumpai.Tulisan ini dimaksudkan untuk mengetahui mengapa masih banyak terjadi perkawinan tidak tercatat di Indonesia dan Malaysia? Penelitian ini berbentuk kualitatif dalam artian penelitian ini tidak untuk mencari seberapa banyak jumlah (kuantitas) orang yang melakukan perkawinan tidak tercatat di Indonesia dan Malaysia, melainkan penelitian ini lebih ditujukan untuk menelaah secara mendalam mengapa masih banyak perkawinan tidak tercatat di Indonesia dan Malaysia, kemudian bagaimana solusi terhadap perkawinan terlanjur tidak tercatat.Temuan penelitan ini menunjukkan banyaknya perkawinan tidak tercatat di Indonesia disebabkan oleh pertama: Ambigunya aturan pencatatan perkawinan dalam perudang-undangan. Kedua: Lemahnya sanksi hukum terhadap pelaku. Sanksi hukum yang diterapkan saat ini lebih berdampak kepada istri dan anak yang dilahirkannya sementara suami hampir tidak merasakan dampak negatifnya. Sementara di Malaysia meskipun aturan yang terdapat dalam enakmen maupun dalam akta undang-udang sangat ketat mengatur agar perkawinan itu tercatat namun terdapat celah hukum yang dimamfaatkan oleh warga Malaysia, yaitu bolehnya menikah di tempat yang jaraknya lebih dari dua marhalah, kemudian perkawinan tersebut dapat kembali didaftarkan setelah terlebih dahulu melalui proses persidangan dan membayar denda di Mahkamah Syariah.